Analisis Pendidikan Kewirausahaan di Sekolah Menengah Kejuruan - Subijanto -- (Jurnal Pendidikan dan Kebudayaan, 2012)
The objective of this article is to analyze the development of implementation for entrepreneurship education at senior vocational school. The problem formulation of this article are as follow: 1) how is the condition of facilities and infrastructure for implementation of entrepreneurship education at senior vocational school?; 2) how is the model of collaboration between Senior Vocational School and business/industry?; 3) how is the management of Senior Vocational School particularly for the implementation of entrepreneurship education? The result of analysis shows that: 1) the implementation of entrepreneurship education has not yet supported by sufficient facilities and infrastructure for training/practice; 2) collaboration model for the implementation of entrepreneurship education between Senior Vocation School and business or industry has not formulated operationally; and 3) the vocational education has not yet managed optimally, particularly in term of collaboration and sharing of various learning facilities. ABSTRAK Tujuan penulisan artikel ini dimaksudkan untuk menganalisais perkembangan pelaksanaan pendidikan kewirausahaan di SMK. Permasalahan yang dirumuskan: 1) bagaimana kondisi sarana dan prasarana pelaksanaan pendidikan kewirausahaan di SMK?; 2) bagaimana pola kerjasama yang dilakukan antara SMK dengan dunia usaha/dunia industri? 3) bagaimana pengelolaan SMK khususnya dalam penyelenggaraan pendidikan kewirausahaan? Hasil analisis menunjukkan bahwa: 1) penyelenggaraan pendidikan kewirausahaan belum didukung oleh sarana dan prasarana pelatihan/praktik yang memadai; 2) pola kerjasama penyelenggaraan pendidikan kewirausahaan antara SMK dengan dunia usaha dan industri (DUDI) belum dirumuskan secara operasional; dan 3) penyelenggara pendidikan kejuruan belum dikelola secara optimal, khususnya dalam hal kerjasama dan sharingberbagai sarana pembelajaran.